Normal filum terminale thickness in newborns: sonographic screening (Annals of Medical Research, 2021)
Aim: The filum terminale is a fibrovascular structure formed of long bundles of 5-20 micron thickness bound to each other with collagen bands. The filum terminale ends between L5 and S3. Our aim in this study, the aim is to sonographically identify normal filum terminale thickness in newborns.
Keywords: Newborn; Ultrasound; Filum Terminale.